An emended description of Piper cochleatum and a new species of Piper (Piperaceae) from the Amazonian slopes of the Colombian Andes - Trujillo Calderón, William; Jaramillo, M. Alejandra (Phytotaxa, 2019)
Piper cochleatum is restored as a distinct species from Piper obtusilimbum, provided with an emended description, and an epitype is designated. The taxon Piper lineatipilosum is also newly synonymized under P. cochleatum. In addition, a new species, Piper caranoense is described from the Andean premontane forests on the Amazonian (eastern) slopes in Colombia. Piper caranoense can be distinguished from Piper cordulatum based on its sarmentose habit and pinnately nerved leaves in the lower third vs. shrubs or small trees with pinnately nerved leaves throughout. An illustration of each species is presented and the morphological differences with similar species are discussed in detail.